Different sources of nitrogen fertilizer in rainfed maize grown in a semiarid environment - Araújo, Maria Diana Melo; Primo, Anaclaudia Alves; Fernandes, Jose Kioma Sousa; Vieira, Lucas Vasconcelos [UNESP]; Clark, Marcus Vinícius Guimarães; Guedes, Fernando Lisboa; Pompeu, Roberto Claudio Fernandes Franco; Sagrilo, Edvaldo; Souza, Henrique Antunes de (Taylor & Francis, 2024)
Although nitrogen is the nutrient most required by maize, doses of N lower than those recommended are applied to maize grown in semiarid environments, which limits the achievement of profitable yields. The objective of this study was to evaluate changes in soil fertility, nutritional status and dry matter production of maize plants fertilized with organic and mineral fertilizers in a semiarid region. A factorial experiment was carried out in Sobral, Ceará state, Brazil, in a randomized block design. The factors were two N sources (organic compost and urea), and four N rates: 27.5, 55, 110 and 165 kg ha−1, with three replications. We assessed variables associated with soil fertility, plant nutritional status, chlorophyll content, grain yield and total dry matter production. The highest rates of organic compost resulted in the highest levels of P (17.7 mg dm−3) and K (102.2 mg dm−3) in soil when compared to the control (7.7 and 69.0 mg dm−3, respectively). However, organic compost rates below 110 kg ha−1 of N-equivalent fertilizer were not enough to supply the plants’ demand for P and K. Low N rates promoted a decrease in soil inorganic N in the second year of application. Applying urea to maize plants led to greater dry matter production than organic compost in the second consecutive crop season. The use of organic compost at rates lower than 110 kg ha−1 of N-equivalent fertilizer decreases soil fertility and has no impact on maize dry matter production.
Keywords: nutritional status; Organic fertilization; semiarid region; soil fertility; Zea mays